BALĀGHAH AL-I'TILĀF ʿINDA AL-MUFASSIRĪN - Mohamad Yusuf Ahmad Hasyim; Hassan Abdelalim AbdelGawwad Youssef (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2022)
This study aims to analyze the i'tilāf contained in the verses of the Qur'an from the perspective of the exegetes (mufassir). I'tilāf is one of the studies in ʿilm al-badīʿ, a discipline in Arabic rhetoric (Balāghah). I'tilāf is a topic that is rarely raised in Arabic research topics. Therefore, this qualitative research with library research design seeks to examine i'tilāf by analyzing data in the form of verses of the Qur'an containing i'tilāf. The data come from Qur'anic exegesis, including Ibn ʿĀshūr's Al-Taḥrīr wa-al-Tanwīr, Al-Zamakhsharī's Al-Kashshāf, Al-Alūsī's Rūḥ al-Maʿānī, and Al-Ṭabarī's Jāmiʿ al-Bayān. The researcher found several verses containing i'tilāf and the opinion of the exegetes on the verse. These verses are divided into three types of i'tilāf, namely i'tilāf al-lafẓ wa-al-maʿná, i'tilāf al-lafẓ maʿa al-lafẓ, and i'tilāf al-maʿná maʿa al-maʿná. In addition, the exegetes also mention the verses of the Qur'an, which include īhām al-tanāsub, namely the sentence structure of the Qur'anic verses that resemble i'tilāf.